Differential expression of CD34 in normal colorectal tissue, peritumoral inflammatory tissue, and tumour stroma. Issue 8 (1st August 2000) - Nakayama, Hirofumi; Enzan, Hideaki; Miyazaki, Eriko; Kuroda, Naoto; Naruse, Keishi; Hiroi, Makoto
Abstract : Aims —To investigate the role of CD34 positive stromal cells, namely dendritic interstitial cells, in the desmoplastic stroma formation of malignant epithelial neoplasms the distribution of CD34 positive stromal cells was examined in human colorectal adenocarcinomas, peritumoral inflammatory tissue, and normal tissue. Methods —Forty one surgically resected human colorectal adenocarcinomas and their corresponding peritumoral inflammatory and normal tissues were examined. To distinguish CD34 positive stromal cells from vascular endothelial cells, immunostaining for both CD34 and CD31 was performed. The distribution of myofibroblasts was also analysed immunohistochemically, and double staining with CD34 and α smooth muscle actin (ASMA) was performed. Results —Most of the stromal cells in the normal colorectal submucosa, muscularis propria, subserosa, and perirectal tissue were positive for CD34. In contrast, the peritumoral inflammatory tissue and the tumour stroma had no CD34 positive stromal cells. The distribution of myofibroblasts was almost the same as in the aforementioned series. No stromal cells double positive for CD34 and ASMA were detected in the peritumoral inflammatory tissues. Conclusions —Most stromal fibroblasts are CD34 positive stromal cells (dendritic interstitial cells). In colorectal adenocarcinomas, a lack of CD34 expression in stromal cells is associated with desmoplastic reaction.